Principles of economics - Deviga Vengedasalam; Karunagaran Madhavan (Oxford Fajar, 2013)
The third edition of Principles of Economics provides students with an in-depth understanding of basic microeconomics and macroeconomics concepts. This book is targeted at students pursuing economics courses at local institutions of higher learning. In keeping with the latest developments in the field, this revised edition includes new topics and subtopics, namely the Islamic Economy System, Derived Demand and Composite Demand, Joint Supply; Consumer, Producer Surplus and Economic Efficiency; Factors Affecting Aggregate Demand and Aggregate Supply, Money Market Equilibrium, the LM curve, and factors that shift the LM curve. Additionally, authentic case studies have been provided for critical chapters to enable students to relate and apply what they have learnt to real-world contexts.